Atividade da acetilcolinsterase e da porfobilinogênio-sintase e alteração comportamental de ratos expostos à nicotina - Jósê, Aline Segatto (2007)
Tobacco smoking and nicotine replacement therapy are the main form of nicotine exposure. The drug abuse for humans often begins during adolescence and the exposure to nicotine during this phase produces long-term alterations, such as increase in cell replication and differentiation, and apoptosis. Some studies have reported that nicotine exerts important inhibitory actions on eating and body weight gain in humans and animals. However, there are also studies showing that this alkaloid does not alter body weight gain. Contradictory results have also been reported about the actions of nicotine on glycemia, insulin secretion, and glucose tolerance and on the activity of some enzymes, such as porphobilinogen-synthase and acetylcholinesterase. Among the beneficial effects of nicotine, it has been reported that nicotine improves cognitive performance, mainly by increasing attention and learning. The aim of this study was to investigate the effects of nicotine exposure on some biochemical, physiological and behavioral parameters. The animals received since the 30° day of life, 5 injections per day (s.c., 1 ml/ kg weight) of saline (0.9%) or nicotine (total dose: 5 mg/kg/day) applied during the dark period of the cycle (8, 10, 12, 14, 16:00 h) for 28 or 56 days. We analyzed acetylcholinesterase and porphobilinogen-synthase activities, hepatic glycogen and glucose levels and the rats behavior on an open field task at 21 days of treatment. The animals were killed 90 min after the last injection and the tissues were collected and prepared to posterior analyses. The animals exposed to nicotine presented a decrease in body weight gain (at 28 and 56 days) and liver weight (at 56 days), a reduction on the liver glycogen levels but not glucose for both intervals of treatment. This difference of effects suggests that the decrease in liver glycogen levels were not enough to produce a hypoglycemia, once these parameters were analyzed when the animals were fed. The activities of the enzymes porphobilinogen-synthase from blood and liver and blood acetylcholinesterase were not affected by nicotine treatment. Nicotine also did not affect hippocampal and cerebral cortex acetylcholinesterase ctivities in animals injected with nicotine for 28 days. The salt (predominantly G1 form) and detergent (mostly G4 form) fractions showed not be affect for the treatment with nicotine for 56 days. The rats treated with nicotine presented similar number of rearing and crossings in both sessions of the open filed task suggesting that they did not habituate to a new environment. However, they presented similar scores of control group on the latency time and number of fecal boluses. As the phobic behavior was not altered, we can suggest that nicotine adolescent rats present impairment of habituation memory, The results of the present study show that nicotine effects are very specific, impairing the weight gain, energy storage in glycogen form and habituation to a new environment, however not interfere in the acetylcholinesterase and porphobilinogensynthase activities.